Inhibition of the Renin-Angiotensin System Reduces Gene Expression of Inflammatory Mediators in Adipose Tissue Independent of Energy Balance - Mitchell, Caitlin S.; Premaratna, Shirmila D.; Bennett, Garth; Lambrou, Maria; Stahl, Lauren A.; Jois, Markandeya; Barber, Elizabeth; Antoniadis, Christopher P.; Woods, Stephen C.; Cameron-Smith, David; Weisinger, Richard S.; Begg, Denovan P. (Frontiers in Endocrinology, 2021)
Obesity is a growing health problem worldwide. The renin-angiotensin system (RAS) is present in adipose tissue and evidence suggests that it is involved in both diet-induced obesity and the inflammation associated with obesity. The present experiments determined the effect of (1) different angiotensin-converting enzyme (ACE) inhibitors (captopril, perindopril, enalapril) and angiotensin receptor blockers (ARBs: telmisartan, losartan) on adiposity of mice fed a high-fat diet for 28-d; (2) acute treatment with the ACE-inhibitor captopril on gene expression of inflammatory markers in mice fed a high-fat diet (HFD); and (3) short-term (2-d) and chronic (28-d) treatment of ACE-inhibition on energy expenditure (EE) and energy balance in mice fed HFD ad libitum (AL) as well as receiving HFD limited to the amount of calories eaten by controls (pair-fed (PF) group). Body weight, food intake, adiposity and plasma leptin were lower in ACE inhibitor or ARB-treated groups over 28-d compared with HFD untreated mice. Short-term treatment with captopril led to increased EE relative to the level in the PF group. After 28 d, EE was lower in both captopril-treated and PF mice compared with AL, but the effect was greater in the captopril-treated group. Adiponectin was elevated in captopril-treated mice, but not in PF mice, after both 2 and 28 d. Additionally, acute RAS blockade in HFD-fed mice reduced mRNA expression for MCP-1, IL-6, TLR4 and leptin in adipose tissue relative to values in untreated groups. These data demonstrate that ACE inhibition and angiotensin receptor blockade reduce food intake to produce weight loss and suggest that the anti-inflammatory effects of ACE inhibition may be independent of weight loss.